DIGITAL FINANCIAL CAPABILITY AND SOCIAL CAPITAL ON GEN Z FINANCIAL RESILIENCE - Wahidah Halimahnur; Minto Yuwono (EKUITAS (Jurnal Ekonomi dan Keuangan), 2026)
The expansion of the digital economy has increased young people's reliance on technology-based financial services, underscoring the need to understand the determinants of their financial resilience. This study examines the effects of digital financial capability, social capital, and consumptive lifestyle on financial resilience, with financial stress considered as a mediating variable among Generation Z in semi-urban areas. A quantitative explanatory approach was employed, using an online questionnaire to collect data from 128 purposively selected respondents. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrate that digital financial capability and social capital exert a significant positive influence on financial resilience, while a consumptive lifestyle does not. Additionally, financial stress does not mediate the relationships between the independent variables and financial resilience, likely because most respondents continue to receive financial support from their families and face relatively low financial burdens. These results emphasize the critical roles of digital capability and social support in enhancing young people's financial resilience in semi-urban contexts.